: Pembuatan Abon Ikan - Djuanda Hatta; Bernadeth Yosephine Prikilla BR Simangunsong; Agustia Agustia; Uly Farikha Maula; Maslia Nur Fitri (Universitas Serang Raya, 2023)
Tarakan City is a potential area for fishery products where most people still sell their catch to traders. To increase the income of fishermen's families, it is necessary to train marine products processing which is a local resource. Thus, the purpose of this service is to add value to the catch of fishermen. The method of activity carried out is to provide an understanding to the community of the added value generated and direct practice of making shredded fish. From the results of the activity, the results obtained for producing shredded with an experiment of 3 kilograms of each type of fish obtained shredded milkfish products weighing 12 ounces with a potential profit of IDR316,000.00 shredded tuna weighing 13 ounces with a potential profit of IDR336,000.00 and gulamah shredded fish weighing 7 ounces with a potential profit of IDR141,000.00 per production. Likewise, this product was a village product whose main source of raw materials comes from the local area.